2008
DOI: 10.1897/07-252.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the influence of environmental heterogeneity on heavy metal exposure concentrations for terrestrial vertebrates in river floodplains

Abstract: To analyze the influence of environmental heterogeneity on heavy metal exposure concentrations for terrestrial vertebrates in river floodplains, a spatially explicit exposure model has been constructed (SpaCE-model: Spatially explicit cumulative exposure model). This model simulates the environmental use of individual organisms by selecting model cells to be foraged in within a multicelled, heterogeneous landscape. Exposure durations and exposure concentrations are calculated for the selected cells, whereby ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…Spatial variability within habitats has also been studied as part of ecological risk assessment [22][23][24]. These few studies argue against a general rule that species and food chains in one habitat are more vulnerable than in another.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial variability within habitats has also been studied as part of ecological risk assessment [22][23][24]. These few studies argue against a general rule that species and food chains in one habitat are more vulnerable than in another.…”
Section: Discussionmentioning
confidence: 99%
“…Middelkoop, 2002;Walling and Owens, 2003;Baptist et al, 2004;Geilen et al, 2004;Thonon, 2006;Schipper et al, 2008a). The additional value of the present study is that the consequences of management choices with respect to various geomorphological and ecological aspects are evaluated simultaneously as well as cohesively.…”
Section: Biogeomorphological Changesmentioning
confidence: 97%
“…Indeed, studies pertaining to sites that are distinctly different with respect to for example land use or the degree of human disturbance showed that relatively coarse taxonomic arthropod data were sufficient to discriminate between the sites, despite a relatively large degree of taxonomic bifurcation (Biaggini et al 2007;Nakamura et al 2007). The lowland floodplains along the Rhine river in The Netherlands are characterized by considerable environmental heterogeneity, due to both natural processes and human influences (Schipper et al 2008a). On a small spatial scale, relatively large differences can be found with respect to e.g., elevation, flooding, soil characteristics, and vegetation types.…”
Section: Taxonomic Level Required For Biomonitoringmentioning
confidence: 99%